THE RELATIONSHIP BETWEEN FAMILY CHARACTERISTICS WITH STUNTING INCIDENCE IN WORKING AREA OF PADANG SERAI PUBLIC HEALTH CENTER - Nurul Khairani; Pawiliyah Pawiliyah (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2020)
Background: Under-fives who have stunting have a risk of decreased intellectual ability, productivity, and increased risk of degenerative diseases in the future (Anugraheni & Kartasurya, 2012). Objective: to examine the relationship between family characteristics with stunting incidence of under five children who visited the Integrated Healthcare Center (Posyandu) in working area of Padang Serai Public Health Center (Puskesmas) of Bengkulu City. Methods: this study was conducted in June, 2016. The type of the study was Analytical Survey and the design was Cross Sectional. Sample was under five children aged 0-59 months (stunted and non-stunted) who visited the Integrated Healthcare Center in working area of Padang Serai Public Health Center of Bengkulu City with their mothers. The sampling technique was Accidental Sampling and the sample total was 92 under five children. The data were primary and secondary data. The primary data were length or height, age of children, and family characteristics (education and knowledge of mothers, number of family, income rate of household heads). The secondary data was collected from Health Department and Integrated Healthcare Center. The data was analyzed with univariate and bivariate analysis. Bivariate analysis used Chi-Square (χ2) test. Results: The prevalence of stunting incidence was 27.17%, no relationship between family characteristics [height of mother (p=0.054), education of mother (p=0.857), knowledge of mother (p=1.000), total of family members (p=0.934), and income rate of household head (p=1.000)] with stunting incidence of under five children who visited the Integrated Healthcare Center in working area of Padang Serai Public Health Center of Bengkulu City.Conclusion: Padang Serai Public Health Center should be able to overcome the stunting problem by doing more intensive nutrition program for the fertile women, pregnant, and lactating women, under five children, and also socialization of the nutritional status of stunting to the community. Keywords: Family Characteristics, Stunting, Under Five Children.